Biochemical Content of Cambium of Abies nephrolepis Eaten by Bears on the Far East of Russia - I. V. Seryodkin; A. M. Zakharenko; P. S. Dmitrenok; K. S. Golokhvast (Biochemistry Research International)
The peculiarity of bears behavior of stripping of bark is typical for all species. We have described the damage to trees, by Asiatic black bear (Ursus thibetanus) and brown bear (U. arctos) in Primorsky Krai and by brown bears on the Sakhalin Island during 1998–2015. In this study, we studied the damaged bark of the tree only in cases where it was clear that part of the cambium was eaten by bears. Cambium of species Abies nephrolepis is the most preferred for bear consumption in Primorsky Krai. We distinguished very large seasonal fluctuations in the amount of its consumption. The greatest interest of bears in this kind of food is in the summer time. We have analyzed the composition of the cambium of A. nephrolepis. These results suggest that the important purpose of the use of this kind of food is to restore and maintain the normal functioning of the intestines.